2011
DOI: 10.3341/jkos.2011.52.10.1173
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Bacterial Endophthalmitis: Bacterial Culture and Visual Acuity Outcomes

Abstract: Purpose:To evaluate the clinical characteristics of bacterial culture, and visual outcome in patients with acute endophthalmitis. Methods: Clinical records of patients treated for acute endophthalmitis in GNUH from 2000 to 2009 were reviewed. The specimens for culture were obtained from the anterior chamber or vitreous. Clinical outcome measures were bacterial culture, culture rate, and final visual acuity. Results: Cultures (total 59 cases) showed bacterial growth in 37 cases (63%). Among 35 cases vitreous sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
3
2
Order By: Relevance
“…This is because the initial VA of the post-glaucoma surgery endophthalmitis was low due to advanced glaucoma, and the diagnosis of endogenous endophthalmitis was delayed because of other systemic problems. In this study, low initial VA is reported as a risk factor for poor visual prognosis, which is consistent with the findings of EVS and Lee and Park’s study [ 5 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is because the initial VA of the post-glaucoma surgery endophthalmitis was low due to advanced glaucoma, and the diagnosis of endogenous endophthalmitis was delayed because of other systemic problems. In this study, low initial VA is reported as a risk factor for poor visual prognosis, which is consistent with the findings of EVS and Lee and Park’s study [ 5 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of vitrectomy as an early intervention in Netherland study was 25 of 250 cases (10%). However, the rate of vitrectomy in a recent Korean endophthalmitis study was 76.3%, which was similar to our current findings [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among the studies, the largest had 59 total cases and 37 culture-positive cases over the course of about 10 years. The smallest patient population had 18 total cases and 8 culture-positive cases over about 5 years [ 8 , 16 ]. In this context, the present study with its large study population of 174 total cases and 103 culture-positive cases has an advantage in revealing the clinical characteristics of Korean infectious endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e frequency of causative microorganisms in endophthalmitis varies depending on the risk factors for endophthalmitis and its geographic locations. In postcataract endophthalmitis, Staphylococcus has been reported to be the most frequently isolated exogenous pathogen globally including in Korea [9][10][11][12]. In other studies, Streptococcus viridans and Pseudomonas aeruginosa were referred to as common exogenous pathogens of postcataract endophthalmitis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%